Leveraging Blockchain Distributed Capability For Personal Data Security to ensure regulatory compliance in the ecosystem across Business Verticals & Industries - Srivastava, Ashutosh (Digital Repository of Theses - SSBM Geneva, 2024)
With the rise of digitalization, online services now heavily depend on our personal identities, significantly affecting our everyday lives and potentially leading to a 6% economic growth in emerging nations and 3% in developed nations by 2030. This thesis delves into the framework of SSI, which is powered by blockchain technology, and emphasises the important collaboration between investors, issuing authorities, and businesses. Tokens are essential in this ecosystem as they contribute to building trust and ensuring security for all parties involved. Privacy concerns, especially in the United States, give rise to global inquiries regarding the delicate balance between the advantages of digital identity and the need for data protection. Regulations such as GDPR and CCPA have arisen in response to these concerns. The Thesis offers a critical analysis of conventional centralised and federated identity models, emphasising the emergence of SSI. This new approach allows users to possess and manage their identity data using digital signatures and distributed ledgers. This thesis explores the integration of SSI with frameworks such as the Personal Information Protection Act (PIPA), taking into account challenges like interoperability and existing identity systems. The integration has the potential to empower users, decrease administrative workload, and enhance transparency. C2 General In addition, this thesis explores the potential of blockchain technology in revolutionising the protection of personal information. It specifically focuses on its role in developing self-sovereign identity (SSI) systems and decentralising data storage. The decentralised nature of blockchain technology is in line with the principles of GDPR, which guarantees secure and transparent management of identities. This research seeks to contribute to the ongoing discourse surrounding the application of blockchain technology in consent management and data protection. It puts forth practical implementations that have the potential to yield significant advantages for both businesses and society. In conclusion, the thesis recognises the difficulties and factors to consider when implementing blockchain solutions for safeguarding personal data. It discusses concerns such as reputational risks, data security, and consent management. The proposal suggests a model of public-private partnership for a decentralised blockchain solution. It emphasises the potential of this solution to transform businesses by minimising costs and liabilities related to maintaining multiple systems for data compliance.